Trimer stability of Helicobacter pylori HtrA is regulated by a natural mutation in the protease domain - Zarzecka, Urszula; Tegtmeyer, Nicole; Sticht, Heinrich; Backert, Steffen (Medical Microbiology and Immunology, 2023)
The human pathogen Helicobacter pylori is a major risk factor for gastric disease development. Serine protease HtrA is an important bacterial virulence factor that cleaves the cell junction proteins occludin, claudin-8 and E-cadherin, which causes gastric tissue damage. Using casein zymography, we discovered that HtrA trimer stability varies in clinical H. pylori strains. Subsequent sequence analyses revealed that HtrA trimer stability correlated with the presence of leucine or serine residue at position 171. The importance of these amino acids in determining trimer stability was confirmed by leucine-to-serine swapping experiments using isogenic H. pylori mutant strains as well as recombinant HtrA proteins. In addition, this sequence position displays a high sequence variability among various bacterial species, but generally exhibits a preference for hydrophilic amino acids. This natural L/S171 polymorphism in H. pylori may affect the protease activity of HtrA during infection, which could be of clinical importance and may determine gastric disease development.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Helicobacter pylori; HtrA; Proteases; Trimer stability